2003
DOI: 10.1101/lm.67103
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Generalization of Conditioned Eyelid Responses Produced Without Cerebellar Cortex: Implications for Plasticity in the Cerebellar Nuclei

Abstract: In Pavlovian eyelid conditioning and adaptation of the vestibulo-ocular reflex, cerebellar cortex lesions fail to completely abolish previously acquired learning, indicating an additional site of plasticity in the deep cerebellar or vestibular nucleus. Three forms of plasticity are known to occur in the deep cerebellar nuclei: formation of new synapses, plasticity at existing synapses, and changes in intrinsic excitability. Only a cell-wide increase in excitability predicts that learning should generalize broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
(115 reference statements)
6
35
0
Order By: Relevance
“…Consistent with previous studies, we observed no SLRs before training (Fig. 6 B, T1) (Medina et al, 2001;Ohyama et al, 2003). Five sessions of unpaired training failed to promote learning and, importantly, also failed to support the acquisition of SLRs (Fig.…”
Section: Experiments 5: Slrs Are Learned and Associativesupporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with previous studies, we observed no SLRs before training (Fig. 6 B, T1) (Medina et al, 2001;Ohyama et al, 2003). Five sessions of unpaired training failed to promote learning and, importantly, also failed to support the acquisition of SLRs (Fig.…”
Section: Experiments 5: Slrs Are Learned and Associativesupporting
confidence: 80%
“…Thus, the stimulus specificity cannot be attributed to an inability of the white noise to gain access to the AIN. The data suggest that a highly input-specific form of plasticity in the AIN underlies SLRs (Perrett and Mauk, 1995;Ohyama et al, 2003).…”
Section: Experiments 4: the Plasticity Underlying Slrs Is Input Specificmentioning
confidence: 94%
See 2 more Smart Citations
“…1, A, left, and B; P Ͼ 0.05). Lidocaine infusions unmasked shortlatency responses similar to those produced after lesions of cerebellar cortex or infusions of the GABA A receptor antagonists picrotoxin or gabazine into the DCN (Bao et al 2002;Garcia and Mauk 1998;Medina et al 2000aMedina et al , 2001Ohyama et al , 2003aPerrett and Mauk 1995;Perrett et al 1993) (Fig. 1, A , middle, and B, bottom).…”
Section: Cerebellar Cortex and Delay Conditioningmentioning
confidence: 99%